Med Aromat Plants 2019
DOI: 10.35248/2167-0412.19.8.341
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices (KAP) Towards Medicinal Plants among Malaysian Consumers

Abstract: This study aims to assess the knowledge, attitude and practice of consumers towards medicinal plants (MPs). Besides that, this study also determined the association between consumers demographic profiles and MPs practice. A survey was performed among 300 MP consumers (Kelantan=100, Terengganu=100 and Pahang=100) from East Coast Economic Region (ECER) using self-administered questionnaire. The findings indicated that 52% of consumers are females, Muslims and Malay. Most of them living in rural (67%) than urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Surprisingly, the result also found out that the students were interested to practice the traditional uses of plants in order to sustain and preserve the culture. This finding is in comparable to the study of Arumugam [27], which revealed that young people showed a positive attitude towards the usage of herbal medicines and supplements. However, the wrong choice and preparation of traditional medicinal plants were noted among the students in the literatures [28][29].…”
Section: Discussionsupporting
confidence: 88%
“…Surprisingly, the result also found out that the students were interested to practice the traditional uses of plants in order to sustain and preserve the culture. This finding is in comparable to the study of Arumugam [27], which revealed that young people showed a positive attitude towards the usage of herbal medicines and supplements. However, the wrong choice and preparation of traditional medicinal plants were noted among the students in the literatures [28][29].…”
Section: Discussionsupporting
confidence: 88%
“…Medicinal plants are medicinal tools with deep cultural and spiritual meanings for specific communities (Zaidi et al, 2022). The custom of rural communities, especially those living near forests, using natural plants to treat several ailments is a centuries-old practice passed down from generation to generation (Arumugam, 2019).…”
Section: Ethnobotany In the Perspective Of Medicinal Plantsmentioning
confidence: 99%